2022
DOI: 10.1002/ldr.4308
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between the soil bacterial community assembly and gene regulation in salt‐sensitive and salt‐tolerant sweet sorghum cultivars

Abstract: Complex bacterial communities in the rhizosphere play a crucial role in plant growth and stress tolerance. These communities vary across cultivars and external environments. However, the influences of salt stress on the structural composition of bacterial microbiome and gene expression of salt‐sensitive and salt‐tolerant sweet sorghum (Sorghum bicolor L. Moench) cultivars have not been studied sufficiently. Here, we employed a combination of 16S rRNA gene profiling and RNA‐seq analysis to characterize changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…2b and c). The host genotype is an important impetus of microbial community composition, and salt-tolerant cultivars can enlist certain bacterial taxa in saline soil (Wu et al 2022;Li et al 2021). Using LEfSe analysis, we found that OTUs in Hydrogenophaga and Pseudomonas were abundant in the SXY rhizosphere (Fig.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…2b and c). The host genotype is an important impetus of microbial community composition, and salt-tolerant cultivars can enlist certain bacterial taxa in saline soil (Wu et al 2022;Li et al 2021). Using LEfSe analysis, we found that OTUs in Hydrogenophaga and Pseudomonas were abundant in the SXY rhizosphere (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…Cyanobacteria and Acidobacteria have been shown to increase while Actinobacteria and Chloro exi decrease in the groundnut rhizosphere upon salt stress (Xu et al 2020). The abundance of Actinobacteria and Gemmatimonadetes is elevated in the rhizosphere of salt-tolerant sweet sorghum, while Bacteroidetes and Firmicutes accumulate in the rhizosphere of sensitive cultivars (Wu et al 2022). Recently, Yuan et al…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PGPRs, including Azospirillum brasilense , Pseudomonas fluorescens , and Achromobacter piechaudii , play crucial roles in enhancing the salt tolerance of host plants (Hamdia et al, 2004; Mayak et al, 2004; Saravanakumar & Samiyappan, 2007) by improving nutrition absorption, solubilizing phosphate, elevating 1‐aminocyclopropane‐1‐carboxylic acid (ACC)‐deaminase activity, producing siderophores, phytohormones and exopolysaccharides, and activating host antioxidant genes (Gururani et al, 2013; Kumari et al, 2015; Nadeem et al, 2016). Salt stress influences soil microbial diversity and leads to microbiome reassembly in plants (Gao et al, 2021; Singh, 2016; Wu et al, 2022). Cyanobacteria and Acidobacteria increased while Actinobacteria and Chloroflexi decreased in the groundnut rhizosphere upon salt stress (Xu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Cyanobacteria and Acidobacteria increased while Actinobacteria and Chloroflexi decreased in the groundnut rhizosphere upon salt stress (Xu et al, 2020). The abundance of Actinobacteria and Gemmatimonadetes elevated in the rhizosphere of salt-tolerant sweet sorghum, while Bacteroidetes and Firmicutes accumulated in the rhizosphere of sensitive cultivars (Wu et al, 2022). Recently, Yuan et al (2016) used the rhizosphere microbiome of the halophyte Suaeda salsa to help non-host rice withstand saline conditions.…”
mentioning
confidence: 99%